Against Cruise Missile and Pershing-2. Series of 5 postcards addressed to prime-ministers Martens, Schmidt, Thatcher, Van Agt and president Carter - Wanda, (1979)
Against Cruise Missile and Pershing-2. Series of 5 postcards addressed to prime-ministers Martens, Schmidt, Thatcher, Van Agt and president Carter.